Design and Methodology of a Pilot Randomized Controlled Trial of Transcranial Direct Current Stimulation in Acute Middle Cerebral Artery Stroke (STICA) - Pruvost-Robieux, Estelle; Calvet, David; Ben Hassen, Wagih; Turc, Guillaume; Marchi, Angela; Mélé, Nicolas; Seners, Pierre; Oppenheim, Catherine; Baron, Jean-Claude; Mas, Jean-Louis; Gavaret, Martine (Frontiers in Neurology, 2018)
Background – Stroke is a major cause of death and disability worldwide. The related burden is expected to further increase due to aging populations, calling for more efficient treatment. Ischemic stroke results from a focal reduction in cerebral blood flow due to the sudden occlusion of a brain artery. Ischemic brain injury results from a sequence of pathophysiological events that evolve over time and space. This cascade includes excitotoxicity and peri-infarct depolarizations. Focal impairment of cerebral blood flow restricts the delivery of energetics substrates and impairs ionic gradients. Membrane potential is eventually lost, and neurons depolarize. Although recanalization therapies target the ischemic penumbra, they can only rescue the penumbra still present at the time of reperfusion. A promising novel approach is to ‘freeze’ the penumbra until reperfusion occurs. Transcranial direct current stimulation (tDCS) is a non-invasive method of neuromodulation. Based on preclinical evidence, we propose to test the penumbra freezing concept in a clinical phase IIa trial assessing whether cathodal tDCS - shown in rodents to reduce infarction volume- prevents early infarct growth in human acute Middle Cerebral Artery (MCA) stroke, in adjunction to conventional revascularization methods. Methods – This is a monocentric randomized, double-blind and placebo-controlled trial performed in patients with acute MCA stroke eligible to revascularization procedures. Primary outcome is infarct volume growth on diffusion weighted imaging (DWI) at day 1 relative to baseline. Secondary outcomes include safety and clinical efficacy. Significance – Results from this clinical trial are expected to provide rationale for a phase III study. Clinical trial registration – EUDRACT: 2016-A00160-51